Hyperphosphatemia and hs-CRP Initiate the Coronary Artery Calcification in Peritoneal Dialysis Patients. (22nd February 2017) - Shang, Da; Xie, Qionghong; Shang, Bin; Zhang, Min; You, Li; Hao, Chuan-Ming; Zhu, Tongying
Abstract : Background. Coronary artery calcification (CAC) contributes to high risk of cardiocerebrovascular diseases in dialysis patients. However, the risk factors for CAC initiation in peritoneal dialysis (PD) patients are not known clearly. Methods. Adult patients with baseline CaCS = 0 and who were followed up for at least 3 years or until the conversion from absent to any measurable CAC detected were included in this observational cohort study. Binary logistic regression was performed to identify the risk factors for CAC initiation in PD patients. Results. 70 patients recruited to our study were split into a noninitiation group (n = 37 ) and an initiation group (n = 33 ) according to the conversion of any measurable CAC during their follow-up or not. In univariate analysis, systolic blood pressure, serum phosphorus, fibrinogen, hs-CRP, serum creatinine, and triglycerides were positively associated with the initiation of CAC, while the high density lipoprotein and nPCR did the opposite function. Multivariate analysis revealed that hyperphosphatemia and hs-CRP were the independent risk factors for CAC initiation after adjustments. Conclusions. Hyperphosphatemia and hs-CRP were the independent risk factors for CAC initiation in PD patients. These results suggested potential clinical strategies to prevent the initiation of CAC in PD patients.